Childhood risk factors and clinical and service outcomes in adulthood in people with intellectual disabilities - B. Perera; S. Mufti; C. Norris-Grey; A. Baksh; V. Totsika; A. Hassiotis; P. Hurks; T. van Amelsvoort (BJPsych Open)
Background Adults with intellectual disability experience increased rates of mental health disorders and adverse mental health outcomes.